ANALISIS LOYALITAS PERUSAHAAN PADA PT LEGALITAS MUDAH - Cut Aviyanti (2022)
The sustainability of the company is the goal of every company. To achieve this sustainability, there are several aspects that need to be considered. The synergy between the company's image, customer trust, and the company's reputation in the company can affect customer satisfaction and loyalty. The main objectives of this study are to 1) determine the effect of corporate image on customer satisfaction; 2) determine the effect of customer trust on customer satisfaction; 3) determine the influence of the company's reputation on customer satisfaction; and 4) knowing the effect of customer satisfaction on customer loyalty. This study uses a quantitative method. This research was conducted at PT. Legalitas Mudah. The research sample is a customer of PT. Legalitas Mudah amounted to 100 respondents. The instrument used in this research is a questionnaire. Data collection techniques are carried out by means of observation, interviews, documentation, distribution of questionnaires, and library searches. The results showed that the company's image has a significant positive effect on customer satisfaction. These results are evidenced by the value of tcount 2.742 > ttable 1.986. Customer trust has a significant positive effect on customer satisfaction. These results are evidenced by the value of tcount 3.153 > ttable 1.986. Company reputation has a significant positive effect on customer satisfaction. These results are evidenced by the value of tcount 2.322 > ttable 1.986. Customer satisfaction has a significant positive effect on customer loyalty. These results are evidenced by the value of tcount 3.035 > ttable 1.986.